TREE FLORA OF NASHIK CITY (MAHARASHTRA): Life Science-Botany - K.N.GAIKWAD; M.V.MALI (International Journal of Life Science and Pharma Research, 2012)
The present communication gives an account of arboreal plants of Nashik city (Maharashtra). The tree flora of the city comprises 150 angiospermic species belonging to 122 genera and 48 families. The Gymnosperms are poorly represented by three species which are monogeneric belonging to three families. The number of indigenous and exotic taxa is 91 and 62 respectively. The floristic information of the tree flora of Nashik city is now available for the first time with this publication